Brief Report: Oxytocin Enhances Paternal Sensitivity to a Child with Autism: A Double-Blind Within-Subject Experiment with Intranasally Administered Oxytocin - Naber, Fabiënne B. A.; Poslawsky, Irina E.; van IJzendoorn, Marinus H.; van Engeland, Herman; Bakermans-Kranenburg, Marian J. (Journal of autism and developmental disorders, 2013)
Oxytocin seems associated with parenting style, and experimental work showed positive effects of intranasally administered oxytocin on parenting style of fathers. Here, the first double-blind, placebo-controlled, within-subject experiment with intranasal oxytocin administration to fathers of children with autism spectrum disorder (ASD) is presented. Fathers with their typically developing toddler ( n = 18), and fathers of toddlers diagnosed with ASD ( n = 14), were observed in two play sessions of 15 min each with an intervening period of 1 week. In all fathers oxytocin elevated the quality of paternal sensitive play: fathers stimulated their child in a more optimal way, and they showed less hostility which suggests the positive effects of oxytocin on paternal sensitive play irrespective of clinical status of their child.